Univariate and multivariate machine learning forecasting models on the price returns of cryptocurrencies - Dante Miller; Jong-Min Kim (Journal of Risk and Financial Management, 2021)
In this study, we predicted the log returns of the top 10 cryptocurrencies based on market cap, using univariate and multivariate machine learning methods such as recurrent neural networks, deep learning neural networks, Holt's exponential smoothing, autoregressive integrated moving average, ForecastX, and long short-term memory networks. The multivariate long short-term memory networks performed better than the univariate machine learning methods in terms of the prediction error measures.
Keywords: 330; cryptocurrencies; deep learning networks; recurrent neural networks; long short-term memory networks